REFORMASI PARTAI POLITIK DAN SISTEM KEPARTAIAN DI INDONESIA - Lili Romli (Jurnal Politica, 2011)
In this reform era, political parties face questions on institutionalization. Generally, political parties deal with weak institutionalization such as the problems of ideology and platform, cohesiveness and conflict management, as well as their recruitment and cadre system. In addition to this, the existing party system is not compatible with the presidential system so that the elected government could not be effective.